2019
DOI: 10.3390/met9020261
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Correlation between Subsurface Residual Stresses and Manufacturing Parameters in Laser Powder Bed Fused Ti-6Al-4V

Abstract: Subsurface residual stresses (RS) were investigated in Ti-6Al-4V cuboid samples by means of X-ray synchrotron diffraction. The samples were manufactured by laser powder bed fusion (LPBF) applying different processing parameters, not commonly considered in open literature, in order to assess their influence on RS state. While investigating the effect of process parameters used for the calculation of volumetric energy density (such as laser velocity, laser power and hatch distance), we observed that an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…In this case, the plateau starts from τ 0 = 30 µm and σ z values vary between 800 and 900 MPa. These results are in good agreement with a previous study by the authors, where the impact of surface roughness was investigated using a LPBF Ti6Al4V material 57 . In this previous study, the effect of surface roughness on the relaxation of RS is also reported to vanish once the plateau is reached.…”
Section: Lpbfsupporting
confidence: 93%
“…In this case, the plateau starts from τ 0 = 30 µm and σ z values vary between 800 and 900 MPa. These results are in good agreement with a previous study by the authors, where the impact of surface roughness was investigated using a LPBF Ti6Al4V material 57 . In this previous study, the effect of surface roughness on the relaxation of RS is also reported to vanish once the plateau is reached.…”
Section: Lpbfsupporting
confidence: 93%
“…It should be noted that a linear interpolation was applied to combine the surface measurement positions and the neutron data in Figure 9. Therefore, any possible sub-surface tensile peaks that had been reported by Mishurova et al [11,34] in LPBF Ti-6Al-4V were not be taken into account in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The chosen setup was identical to the one used in previous measurements [ 12 , 13 , 16 ]. All measurements were conducted in reflection at a diffraction angle of 2θ = 8°.…”
Section: Methodsmentioning
confidence: 99%
“…The scan strategies and laser parameters in LPBF also strongly influence the formation of residual stresses (RSs) [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The origins of the RS in AM are the steep and local thermal gradients developing during melting, remelting, reheating, solidification, and cool-down (see further Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation